Расчет номинальной площади контакта острого резца с круглой режущей кромкой и обрабатываемой поверхностью при точении - Мановицкий, А.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
There are good many cylindrical components of machines with grooves, hollow chamfers
etc. are to be machined with single point cutters. It is important to nominate the correct cutting regimes when cutting of hardened steels or welding deposited alloys on the surface of recovered part
with a hardness around 58–63 HRС and rough initial profile of blank. The problem of interaction
between the cutting tool and surface layer of component blank machined is the critical one when
final turning. Mathematical stimulation is one of the ways of researches of process to discover the
nature of action of different technological factors when cutting. To estimate the cutting force main
direction and its components when processing it is important to calculate the contact surfaces of
cutting element of tool with material machined. Results of approaches to the calculation of nominal
contact squares with material of allowance and component machined when turning with round
РcBN insert single point cutters are reported.